Design and Development of a Digital Library Book Lending Information System at Mastrip Jombang with WhatsApp Notification Integration - Nur Khafidhoh; Siti Sufaidah; Abi Muhammad Wahid (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The development of information technology has driven the transformation of library services into more effective and efficient digital systems. One of the common problems faced by libraries is the delay in book returns and the lack of effective communication media between librarians and users/ This study aims to examine the implementation of a digital library book borrowing system integrated with WhatsApp as an automatic notification medium. The research method used is descriptive qualitative with a literature study and system analysis approach. The results indicate that the integration of WhatsApp into the library borrowing system improves the accuracy of borrowing information, reduces delays in book returns, and enhances service quality. Moreover, the system facilitates real-time information delivery through a communication platform that is widely used by users. Therefore, utilizing WhatsApp as a notification medium is a relevant solution for developing digital library services in the information technology era.